Environmental Drivers and Nutritional Impacts of Moricandia arvensis L. as a Winter Nutrition Resource for Honeybees - Ali, Mahmoud; Seddik M. A (Andalasian International Journal of Entomology, 2025)
Understanding the temporal dynamics of pollinator activity is critical for conserving ecological interactions in Mediterranean ecosystems, where resource scarcity intensifies during winter. This study examines diurnal and seasonal variations in bee visitation to Moricandia arvensis (Brassicaceae), a key winter-flowering species, and assesses the environmental factors influencing pollinator behavior. Over seven weeks (October–December 2023), bee visits were recorded three times daily (9:00 am, 12:00 pm, 3:00 pm) in Qena, Egypt, alongside measurements of temperature, humidity, wind speed, and atmospheric pressure. Results revealed pronounced diurnal patterns, with peak visitation at midday (12:00 pm: 21.40 ± 2.51 visits), significantly exceeding morning and afternoon rates (F = 176.32, p < 0.001). Seasonal activity declined sharply, dropping from 18.13 ± 0.51 visits/week in late October to 4.73 ± 0.20 by late November. Visitation correlated strongly with atmospheric pressure (r ≈ 0.99) and wind speed (r = 0.98–1), while temperature (r = -0.85 to -0.88) and humidity (r = -0.62 to -0.88) exhibited negative associations. Species-specific responses emerged: Andrena sp. foraged predominantly in mornings (27.00 ± 2.16 visits at 9:00 am), whereas squash bees (Peponapis spp.) peaked later (6.20 ± 1.17 visits at 12:00 pm). Pest pressures from Spilostethus pandurus and Lampides boeticus reduced floral viability, exacerbating seasonal declines. These findings underscore M. arvensis as a critical autumn resource for pollinators, bridging floral scarcity until winter. However, its utility diminishes under colder, humid conditions, highlighting vulnerability to climate shifts. Conservation strategies prioritizing arid-adapted flora, such as M. arvensis, in conjunction with integrated pest management, could enhance pollinator resilience in Mediterranean agroecosystems.